2015
DOI: 10.1103/physrevlett.115.118301
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Varying Permittivity on the Conductivity of Polyelectrolyte Solutions

Abstract: Dissolved ions can alter the local permittivity of water; nevertheless most theories and simulations ignore this fact. We present a novel algorithm for treating spatial and temporal variations in the permittivity and use it to measure the equivalent conductivity of a salt-free polyelectrolyte solution. Our new approach quantitatively reproduces experimental results unlike simulations with a constant permittivity that even qualitatively fail to describe the data. We can relate this success to a change in the io… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 68 publications
0
32
1
Order By: Relevance
“…In a more realistic, orientation of water molecules near the binding sites, polar groups composing the ligand itself, and the salt concentration would influence the local dielectric constant and thus, ionic distributions [50,51]. Indeed, recently it has been shown that ionic mobility in salt solutions can be described more accurately with a non-uniform dielectric constant [52]. Similar effects can alter unbinding rates by pushing the ions from the binding site or increasing diffusion coefficient within the ionic atmosphere.…”
Section: Implicit Simulations Can Underestimate Contact Energiesmentioning
confidence: 99%
“…In a more realistic, orientation of water molecules near the binding sites, polar groups composing the ligand itself, and the salt concentration would influence the local dielectric constant and thus, ionic distributions [50,51]. Indeed, recently it has been shown that ionic mobility in salt solutions can be described more accurately with a non-uniform dielectric constant [52]. Similar effects can alter unbinding rates by pushing the ions from the binding site or increasing diffusion coefficient within the ionic atmosphere.…”
Section: Implicit Simulations Can Underestimate Contact Energiesmentioning
confidence: 99%
“…If the gradient of the locally varying permittivity ε(r) is non-zero, this energy leads to a force that is included in the HIM method presented in our earlier work with Xu 41 and the electrostatic algorithm used in this manuscript. In this article, we expand on our previous study on the conductivity of polyelectrolyte solutions with a locally varying permittivity 59 . We first introduce the new electrostatic algorithm in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Both of these may be brought about by the addition of either ionomer or acid. 50 However, both of these are closely related to pH in these systems. Dielectric constant and ionic strength may both be changing because of ionic group addition, which is reflected in the dispersion pH.…”
mentioning
confidence: 99%